1981
DOI: 10.1093/infdis/143.3.432
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Activity of Purified Lipopolysaccharide of Neisseria gonorrhoeae for Human Fallopian Tube Mucosa

Abstract: An experimental model of human fallopian tubes in organ culture was used to examine the ability of lipopolysaccharide (LPS) of Neisseria gonorrhoeae to damage the fallopian tube mucosa. Gonococcal LPS was purified by hot phenol-water extraction and sequential ultracentrifugation. This LPS was highly lethal for lead-sensitized mice and at a concentration as low as 6 pg/ml reproducibly gelled limulus amoebocyte lysate. Gonococcal LPS damaged fallopian tube mucosa in concentrations as low as 0.015 microgram/ml, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
58
0

Year Published

1983
1983
2010
2010

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(59 citation statements)
references
References 31 publications
1
58
0
Order By: Relevance
“…In this model it was shown that GC are internalized by nonciliated cells and sequestered within membrane-bound vacuoles which transcytose, fuse with the cells' basolateral membranes, and release the bacteria into the submucosa (22,26,(39)(40)(41)80), where they can initiate an inflammatory reaction and invade the bloodstream to spread systemically.…”
mentioning
confidence: 99%
“…In this model it was shown that GC are internalized by nonciliated cells and sequestered within membrane-bound vacuoles which transcytose, fuse with the cells' basolateral membranes, and release the bacteria into the submucosa (22,26,(39)(40)(41)80), where they can initiate an inflammatory reaction and invade the bloodstream to spread systemically.…”
mentioning
confidence: 99%
“…injluenzae endotoxin. It is interesting that sterile supernatant fluids from fallopian tube organ cultures infected with Neisseria gonorrhoeae similarly cause loss of ciliary activity and sloughing of epithelial cells when transferred to fresh organ cultures Johnson et al, 1977) and Gregg et al (1981) have shown that the active factor in such supernatant fluids is gonoccocal lipopolysaccharide (endotoxin). The role that H .…”
Section: Discussionmentioning
confidence: 99%
“…It is an outer membrane glycolipid involved in immune system evasion, attachment to epithelial tissue, host cell invasion, mediation of toxic damage in the fallopian tube, and stimulation of the production of bactericidal antibodies (2,15,20,41,44,45). Biosynthesis of gonococcal and meningococcal LOS occurs via the same biosynthetic pathway producing a branched oligosaccharide attached to lipid A via two 3-deoxy-D-manno-2-octulosonic acid (KDO) molecules (12,13,21,22,48).…”
mentioning
confidence: 99%